The situation is serious, but not hopeless: Evidence-based considerations on the intracouple division of childcare before, during and after the Covid-19 lockdown - Christina Boll; Simone Schüller (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
Drawing on data from the Socio-economic Panel (SOEP) for 2018, we use a sample of 2,145 heterosexual couples with children below age 13 to investigate the paternal involvement in domestic childcare and the relation of the underlying mechanisms to the two job-related "Covid-19 factors" systemic relevance (SR) and capacity to work from home (WfH). Based on bi- and trivariate analyses of the intra-couple distribution of time, income and gender roles before the crisis and their likely change during the pandemic depending on parents' job characteristics SR and WfH, we nominate three couple constellations which are most likely to manifest an increase in the proportion of paternal childcare in the post-pandemic period. Depending on the specification of access to emergency care, we quantify a share of 7-8% of couples as 'sources of hope'. We further expect positive impulses for gender equality not only in the private but also in the corporate sphere, especially through multiplier effects, which are likely to emanate from fathers in managerial positions.
Keywords: D13; J13; J16; 330; Covid-19; intra-couple division of unpaid work; systemic relevance; work from home; childcare; SOEP